A Human-Robot Collaboration Framework for Improving Ergonomics During Dexterous Operation of Power Tools. (April 2021) - Kim, Wansoo; Peternel, Luka; Lorenzini, Marta; Babič, Jan; Ajoudani, Arash
Highlights: A human-robot collaboration takes into account ergonomic aspects of the human co-worker during power tool operations. The human overloading joint torques are estimated and monitored online using a whole-body dynamic state model. The collaborative robot motion that brings the human into the suitable ergonomic working configuration is obtained by an optimisation method to minimise the overloading joint torques. The human arm muscular manipulability and safety of the collaborative task are used in the optimisation process as the constraints to achieve a task-relevant optimised configuration. An ergonomic human-robot collaboration framework enable to provide not only the co-worker's lower joints overloading effect but also high manipulability capacity. Abstract: In this work, we present a novel control approach to human-robot collaboration that takes into account ergonomic aspects of the human co-worker during power tool operations. The method is primarily based on estimating and reducing the overloading torques in the human joints that are induced by the manipulated external load. The human overloading joint torques are estimated and monitored using a whole-body dynamic state model. The appropriate robot motion that brings the human into the suitable ergonomic working configuration is obtained by an optimisation method that minimises the overloading joint torques. The proposed optimisation process includes several constraints, such as the human arm muscular manipulability and safety of the collaborative task, to achieve a task-relevant optimised configuration. We validated the proposed method by a user study that involved a human-robot collaboration task, where the subjects operated a polishing machine on a part that was brought to them by the collaborative robot. A statistical analysis of ten subjects as an experimental evaluation of the proposed control framework is provided to demonstrate the potential of the proposed control framework in enabling ergonomic and task-optimised human-robot collaboration.